Perempuan dalam Perspektif al-Qur’an - M. Najihun Naja; Hadi Mungawan, Samsul; Muhamad, Fahmi (Shād : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
In the Qur'an, women actually have the same status as men. Generally, in Muslim society, women are considered to have a status one level below men. This arises partly from the construction of classical interpretations that are gender-biased and patriarchal, so that these interpretations often result in women being unable to participate in the public sphere. Therefore, women are often marginalized by men, women's rights and freedoms are bound by men. In contrast to classical interpretation methods, the development of modern interpretations has given rise to contextual interpretations using the hermeneutic method in interpreting women within the framework of the Qur'an. The results of this study show that the Qur'an upholds the values ​​of justice and honesty, including in the context of gender relations, emphasizing that justice does not mean absolute equality, but rather treatment that is appropriate to the needs and responsibilities of each. Based on the various references to women, women and men are actually equal. Women can also be like men, they can also be in the public sphere. Therefore, today women can also play a role, whether in politics, government, and other positions. Keywords: The Qur’an, Women, Gender